2016
DOI: 10.1109/tpds.2015.2486772
|View full text |Cite
|
Sign up to set email alerts
|

Eavesdropping Prevention for Network Coding Encrypted Cloud Storage Systems

Abstract: Network coding is an important cloud storage technique, which can recover data with small repair bandwidth and high reliability compared to the existing erasure coding and replication methods. However, regardless of which data recovery technique is used, the repaired data in a geographically distributed cloud storage system are easy to be eavesdropped at the transmission link between the local datacenter and its remote backup site. This kind of network security issue is called link eavesdropping in this paper.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous works have shown that network coding can provide robustness [24]- [26] and improve throughput [25], [27] as well as confidentiality [28]. More recently, network coding is employed to improve the security and reliability of distributed storage systems such as recovering lost data in multiple storage nodes [29], preventing eavesdropping over untrusted networks [30] and checking integrity of outsourced data [31].…”
Section: Objective Of This Papermentioning
confidence: 99%
“…Previous works have shown that network coding can provide robustness [24]- [26] and improve throughput [25], [27] as well as confidentiality [28]. More recently, network coding is employed to improve the security and reliability of distributed storage systems such as recovering lost data in multiple storage nodes [29], preventing eavesdropping over untrusted networks [30] and checking integrity of outsourced data [31].…”
Section: Objective Of This Papermentioning
confidence: 99%
“…For secure storage over multiple clouds, similar to this work, the authors of [3] proposed a security protection scheme to ensure that no symbols can be decoded by an eavesdropper, which is weaker than perfect secrecy. In [23], a link eavesdropping problem in a networkcoded cloud storage system was investigated. A publicly verifiable protocol for network coded cloud storage was proposed in [24].…”
Section: B Network Coding For Data Securitymentioning
confidence: 99%
“…For example, in the intelligent transportation system, eavesdroppers infer the path planning of vehicles by monitoring the location information, and on this basis, eavesdropping attacks will easily succeed [17,18]. In terms of existing research, data encryption is the main method to protect system privacy from eavesdropping attacks [19][20][21].…”
Section: Introductionmentioning
confidence: 99%